PENENTUAN JURUSAN SISWA SMK DENGAN MENERAPKAN METODE SIMPLE ADDITIVE WEIGHTING - Juansen, Monsya (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2021)
The suitability of the major chosen by a student is one of the factors supporting the successful achievement of vocational school graduates, so that in order to realize the accuracy of this major, the researcher built a decision support system for determining the major. In this study, the data that was managed was data from class 1 students in the field of Computer Engineering and Information Technology who would go up to grade 2, because majors were carried out when students went up to grade 2, which would later be divided into 3 majors, these majors were Computer Engineering, and Networking, Multimedia, and Software Engineering. This study applies a decision support system with the Additive Weighting Method (SAW) algorithm. This research is very helpful for the school in providing majort recommendations to students so that students are in the right major according to the talents that exist in students.